Design of a novel walking assistance device for people with walking disabilities - Rafighi, Mohammad; Güllü, Abdulkadir (International Journal of Engineering and Technology, 2017)
Moving independently is very important for people with walking disability, thus, in this paper the novel walking assistance device is designed based on strategies derived from optimization of available walking assistance devices for ‎the people with walking disabilities. Available walking assistance device like ReWalk has high price and heavy weight disadvantages. Therefore, the main aim of this study is optimization of available devices by new design and analyses to make them cheaper and lighter. The presented device is a simulator of a human body motion in lower limb which consists of ‎ hip, shank and knee. All parts were designed and assembled in software module and after manufacturing, it could be used as a rehabilitation device for the people with walking disability to support their sitting, standing and walking. As a result, regarding to aforementioned issues, in this study the new walking assistance device was designed which is inexpensive and light weight.